PERAN KETERAMPILAN NEGOSIASI TERHADAP MANAJEMEN KONFLIK MELALUI INTERMEDIASI EFEKTIVITAS KOMUNIKASI - Yayan Hendrayana (PARAMETER, 2020)
This study examines the role of negotiation skills on conflict management through intermediation of communication effectiveness, using a saturated sample of 90 respondents and the research method using structural equation analysis and path analysis. The software used is SMART PLS 3.0. The results of this study indicate that there is a significant influence between the role of negotiation skills on conflict management through effective communication intermediation. This role, either partially or simultaneously or through the intermediation process, is proven to have a positive and significant effect. So that if you see these facts, it is hoped that the management must continue to develop the negotiation skills of its employees and also contribute to building an effective communication role so that it will certainly help the conflict management process as an instrument for solving problems in the field.